Everyday Life Information Behavior, Health Information Seeking, and HIV and STI Awareness among People Who Inject Drugs (PWID) - Shuva, Nafiz Zaman; Taisir, Radia; Mallick, Parvez Sazzad (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
This study aims to explore the everyday life and health information behavior of people who inject drugs (PWID) in Bangladesh, as well as the effectiveness of HIV and STI informational programs in promoting safe injecting and sexual behavior. The study received 97 completed survey responses and conducted two focus group discussions (FGDs) with 13 PWID. Using de Certeau’s everyday life practices framework, the study aims to understand the tactical information strategies of PWID in the context of a developing country where access to government services and trust in authorities may be significantly limited among marginalized populations. PWID’s information needs focused primarily on drug-related information, personal safety, and health-related information. They consult mainly other PWID and NGO workers to meet their information needs. However, the findings also suggest that PWID are experiencing significant unmet information needs. For their health information/services, they reported mainly using local pharmacies and NGO clinics. Although PWID claimed to participate in HIV and STI prevention programs and events, their needle/syringe use and sexual practices suggest that current informational programs may be less effective than intended in promoting safe injecting and sexual behavior. The findings of this study contribute to the understanding of the vulnerability of PWID in accessing information and the limitations of informational programs in specific contexts, with implications for interdisciplinary researchers and agencies working to address the rapid spread of HIV and other infections among PWID in developing countries. Further research is warranted to examine the underlying motivational factors that contribute to the practice of unsafe needle and syringe sharing, as well as risky sexual behaviors, among vulnerable populations such as PWID, despite their awareness of the associated risks.